2021
DOI: 10.17323/jle.2021.11020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computer-assisted L1 and L2 Textual and Audio Glosses on Vocabulary Learning and Reading Comprehension across Different Learning Styles

Abstract: The current study investigated the effects of computer-assisted L1 and L2 textual and audio glosses on vocabulary learning and reading comprehension across various learning styles. Based on the PET test, 30 homogeneous Iranian EFL learners took the VARK questionnaire and were divided into five learning style groups. Twenty-eight words were selected to be glossed in four reading passages. The selected passages, which were glossed in the four different forms of L1 and L2 audio and L1 and L2 textual by creating h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This matched instruction differs depending on the learning style of the student. In the current meta-analysis, approximately one-fourth of the learning measures indicated a crossover interaction in which there were positive effect sizes for matched instruction for two different learning styles ( Kassaian, 2007 ; Chen and Sun, 2012 ; Hazra et al, 2013 ; Kam et al, 2020 ; Lehmann and Seufert, 2020 ; Chui et al, 2021 ; Tadayonifar et al, 2021 ). This raises the question of what characteristics of these studies and learning measures may be responsible for the crossover interaction.…”
Section: Discussionmentioning
confidence: 65%
“…This matched instruction differs depending on the learning style of the student. In the current meta-analysis, approximately one-fourth of the learning measures indicated a crossover interaction in which there were positive effect sizes for matched instruction for two different learning styles ( Kassaian, 2007 ; Chen and Sun, 2012 ; Hazra et al, 2013 ; Kam et al, 2020 ; Lehmann and Seufert, 2020 ; Chui et al, 2021 ; Tadayonifar et al, 2021 ). This raises the question of what characteristics of these studies and learning measures may be responsible for the crossover interaction.…”
Section: Discussionmentioning
confidence: 65%
“…Having investigated the effects of glossing type, language, and learning style on vocabulary and reading comprehension, Tadayonifar et al (2021) found that with intermediate level EFL students (19-20 ages) L1 textual glosses are deemed more effective than L2 glosses because of the relative ease of understanding L1 glosses. L2 glosses require high working memory capacity (Varol & Erçetin, 2021), and can be useful as long as they are designed to be brief, comprehensible, and suited to the learners' proficiency level, and then they may have a globally wide range of uses, together with mixed L1 classes (Boers, 2021).…”
Section: Dictionaries and Glossingmentioning
confidence: 99%
“…Glosses are placed in different locations with changing effects; either at the end of a text -as a glossary-, inside a text -as appositives or definitions-, or in the margin close to the line of the focused word, which is relatively more preferable than the previous two ways in the sense that learners reach the information and return to reading faster. A gloss may contain a very brief, clarifying text in L1 or L2, a picture, a combination of the two, a multiple-choice question related to the contextual meaning of the target item, an audio, or a video clip with or without definition text (Tadayonifar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%